Synthesis of Biohybrid Particles by Modification of Chitosan Beads via RAFT Polymerization in Dispersed Media. Issue 6 (2nd August 2020) - Solimando, Xavier; Champagne, Pascale; Cunningham, Michael F.
Abstract: Spherical macroscopic particles (beads) made from chitosan (CTS), a polysaccharide derived from the valorization of food waste, are converted into a biohybrid material by grafting poly(4‐vinylpyridine) (P4VP) using a "grafting from" approach via reversible addition–fragmentation chain‐transfer (RAFT) polymerization. Varying the time of reaction, and therefore the conversion, allows to readily tune the composition (CTS vs synthetic polymer content) and consequently the bead properties. P4VP has specific affinity for certain compounds. Thus, the biohybrid particles are promising candidates for applications related to (waste) water treatment, sensors, or biomedical fields. In this study, the potential use of CTS‐g‐P4VP particle beads for the removal of an emerging contaminant of concern (bisphenol A) from water is demonstrated. It is shown that removal efficiency is enhanced from 25% to 70% by the grafting of P4VP on CTS. Abstract : Particles are prepared from chitosan and decorated with poly(4‐vinylpyridine) via reversible addition–fragmentation chain‐transfer polymerization in heterogeneous media. Composition of the biohybrid particles can be readily tuned by adjusting time of reaction. The modification of chitosan allows to increase more than 3 times its ability to adsorb emerging contaminant (bisphenol A) in water.